An analysis of open innovation determinants: The case study of Singapore based family owned enterprises - KOH, Annie (Institutional Knowledge at Singapore Management University, 2019)
Family businesses play an important role in the growth of global economy, and while they are arguably perceived as a conservative form of organization with high risk aversion and reluctance to change, counterintuitive empirical evidence show that they are most effective in ideation and commercialization of innovation projects. In the current business environment of rapid change in work patterns, fast adoption of enabling technologies for seamless collaborations across industry and geography, along with intense competition and high uncertainty, enterprises have no choice but to maximize returns on innovation investments. Therefore, they are increasingly dependent on an ecosystem-based approach to innovation management, which has shown greater likelihood to create radical innovations and enable profit generation. The objective of this paper is to analyse determinants of open innovation practices in family-owned enterprises in consideration of the joint effect of in-company enablers and external factors. Drawing on a sample of 33 Singapore based family-owned firms, our findings confirmed the key drivers such as family and business culture, access to external funds, government supported initiatives, market dynamics, partnership, network, family capital, and external network. Managerial implications about the necessity to leverage both environmental determinants and internal innovation capabilities to foster novel business ideas are also highlighted in the conclusion of the paper.